Responses of Montane Forest to Climate Variability in the Central Himalayas of Nepal - Mainali, Janardan; All, John; Jha, Pramod Kumar; Bhuju, Dinesh Raj (Mountain research and development, 2015)
Climate changes are having dramatic ecological impacts in mid- to high-latitude mountain ranges where growth conditions are limited by climatic variables such as duration of growing season, moisture, and ambient temperature. We document patterns of forest vegetative response for 5 major alpine forest communities to current climate variability in the central Himalayas of Nepal to provide a baseline for assessment of future changes, as well as offer some insight into the trajectory of these changes over time. We used mean monthly surface air temperature and rainfall and the monthly averaged normalized difference vegetation index (NDVI) to compare relative vegetation productivity among forest types and in relation to both climatic variables. Because changes in temperature and precipitation are directly manifested as changes in phenology, we examined current vegetative responses to climate variability in an effort to determine which climate variable is most critical for different alpine forest types. Our results show that correlations differ according to vegetation type and confirm that both precipitation and temperature affect monthly NDVI values, though more significant correlations were found with temperature data. The temperature response was more consistent because at the maximum increased temperatures, there was still an ongoing increase in vegetative vigor. This indicates that temperature is still the major limiting factor for plant growth at higher-elevation sites. This part of the Himalayas has abundant moisture, and some forest types are already saturated in terms of growth in relation to precipitation. Clear increases in productivity are documented on the upper treeline ecotones, and these systems are likely to continue to have increasing growth rates.